2020
DOI: 10.31557/apjcp.2020.21.9.2723
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obesity on Response to Neoadjuvant Therapy in Locally Advanced Gastric Cancer

Abstract: Introduction: The effect of obesity on response to neoadjuvant chemotherapy (NACT) remains unknown. We aimed to investigate the effect of obesity on response to NACT and survival in locally-advanced gastric cancer (GC). Methods: From 2010 to 2019, 142 GC patients with clinical stage III disease who underwent curative surgery after NACT were enrolled. Patients were divided into 3 groups according to body mass index (BMI) as follows; BMI < 25 kg/m 2 , BMI = 25-30 kg/m 2 , and BMI > 30 kg/m 2. The Mandard tumor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…For locally-advanced GC, the phase III MAGIC study performed in 2006 which demonstrated survival bene t of NACt over surgery alone has been a milestone in this area, leading to a positive trend towards NACt, and the results of this study were supported by recent clinical trials from [4]. Moreover, recent studies have shown that NACt is well tolerated and does not affect postoperative morbidity and mortality in GC patients [9,10].…”
Section: Introductionsupporting
confidence: 54%
“…For locally-advanced GC, the phase III MAGIC study performed in 2006 which demonstrated survival bene t of NACt over surgery alone has been a milestone in this area, leading to a positive trend towards NACt, and the results of this study were supported by recent clinical trials from [4]. Moreover, recent studies have shown that NACt is well tolerated and does not affect postoperative morbidity and mortality in GC patients [9,10].…”
Section: Introductionsupporting
confidence: 54%
“…There were 38 studies 43,45,46,59‐91,211,212 (40 cohorts; 2,361,275 participants) of cancer populations (Table S3); 17 cohorts were in East Asia, 10 cohorts in North America, 7 in Europe, 2 were international cohorts, 2 were in West Asia, and 1 each in South America and Africa. Mean age of participants ranged from 17 to 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that survival was better in patients who received neoadjuvant treatment and achieved a response. [37] In our study, although there was no comparator arm in the BSC programme, we believe that this patient population should not be left untreated because OS was 10.5 months in patients with ECOG PS 0-1, 13.8 months in patients receiving two lines or more, and the frequency of side effects was acceptable. As there are acceptable survival outcomes even with single-agent therapies, monotherapy should be recommended for patients with poor ECOG PS and combination therapies for patients with good PS without comorbidities.…”
Section: Discussionmentioning
confidence: 71%